2011
DOI: 10.1177/1756287211418722
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for high-risk localized prostate cancer

Abstract: Treatment of men with high-risk prostate cancer (PCa) remains challenging for urologists. The complex natural history of high-risk PCa and the lack of specific and accurate definitions for high-risk disease impede treatment decision making. Historically, surgery in this patient group has been avoided based on the perception of ostensibly higher complication rates associated with inferior functional and oncological outcomes. To date, no randomized data comparing different therapy approaches have been made avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
1
7
1
Order By: Relevance
“…21 Thus, we agree with the conclusion of Schmitges et al that the perception of higher rates of urinary incontinence, erectile dysfunction, and perioperative complications after a RP in high-risk patients is not supported by the current literature. 28 Neurovascular bundle-sparing during roboticassisted laparoscopic radical prostatectomy In our study 94 of 300 patients underwent a bilateral NVB-sparing procedure with RARP. Not surprisingly, there was a higher incidence (71.9%) of patients undergoing a bilateral NVB preservation in the low-risk group compared to the intermediate-(38.6%) and high-risk (9.4%) groups.…”
Section: Trifecta Outcomes and Risk Classificationmentioning
confidence: 91%
See 1 more Smart Citation
“…21 Thus, we agree with the conclusion of Schmitges et al that the perception of higher rates of urinary incontinence, erectile dysfunction, and perioperative complications after a RP in high-risk patients is not supported by the current literature. 28 Neurovascular bundle-sparing during roboticassisted laparoscopic radical prostatectomy In our study 94 of 300 patients underwent a bilateral NVB-sparing procedure with RARP. Not surprisingly, there was a higher incidence (71.9%) of patients undergoing a bilateral NVB preservation in the low-risk group compared to the intermediate-(38.6%) and high-risk (9.4%) groups.…”
Section: Trifecta Outcomes and Risk Classificationmentioning
confidence: 91%
“…Schmitges et al suggested that performing a NVB-sparing procedure seems to be oncologically safe, only if patients are properly selected. 28 On the contrary, Antebi et al reported that the BCR-free and trifecta rates significantly decreased from low-, then intermediate-, and lastly, to high-risk patients 54 months after a RRP. 21 Pierorazio et al reported that the BCR-free rate was 96.4, 90.3, and 78.7% in the low-, intermediate-, and high-risk groups, respectively, at a median follow-up period of 4.4, 4.8, and 7.1 years after RRP, respectively (P < 0.001).…”
Section: Trifecta Outcomes and Risk Classificationmentioning
confidence: 96%
“…Despite the reported advantages of surgery for men with high-risk PC, concerns exist regarding the potential for increased perioperative morbidity in these cases [66]. Importantly, however, numerous series have now demonstrated similar morbidity rates following RP across disease risk stratifications.…”
Section: Safety and Approach To Surgery For High-risk Pcmentioning
confidence: 99%
“…In addition, analysis of the effect of age and comorbidity on treatment outcomes in 2,048 men treated by laparoscopic radical prostatectomy also concluded that the occurrence and severity of short-term postoperative complications were more strongly related to comorbidity than to chronological age [2]. In centers of excellence for the treatment of prostate cancer, patients with high-risk disease do not have an increased risk of postsurgery incontinence compared with other risk groups [30]. Nevertheless, long-term follow-up from the Prostate Cancer Outcome Study, a cohort of unselected populationbased patients in the U.S., suggests that older men have a significantly higher decline in urinary function following radical prostatectomy compared to younger ones [31].…”
Section: Complications Of Surgery For High-risk Prostate Cancermentioning
confidence: 99%